(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
We do not want to be the last pessimists nor the first optimists, but dealing with established scientific facts without exaggeration represents the first step to overcome crises and disasters. Currently, the emergence of a novel human coronavirus, SARS-CoV-2, has become a global health concern, causing severe respiratory tract infections in humans. The crisis has been made worse by shortages of essential medical supplies, which has led chemists and other researchers all over the world to work hard because there is no vaccine and no effective treatment. Coronavirus attacks all the countries without exception, but it makes specific targets of some parts of the world, such as Italy, Spain, and, before that, China and Iran. In this work we highlight two common parameters that influence the reactivity of the virus, which we depend on to report the kinetic studies and our opinions towards the specificity of the virus with European people.